A STUDY ON THE VOCABULARY LEVEL OF THE THIRD YEAR NATURAL SCIENCE AND SOCIAL SCIENCE STUDENTS OF SMAN 10 PEKANBARU - Reville Dewenora Sinaga; Supriusman Supriusman; Maria Safriyanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is a descriptive-quantitative research design which is aimed to find out the Vocabulary Level of the third year Natural Science and Social Science Students of SMAN 10 Pekanbaru. The subjects of this study were the third year Natural Science and Social Science Students of SMAN 10 Pekanbaru. 244 students taking part in this study were given The New Vocabulary Level Test (NVLT) by Webb et al., (2017). The findings of this study revealed that the student vocabulary level as follows the mean score result, the study shows that the Natural science students have reached the requirement for the 1000 and 2000 vocabulary level of Depdiknas RI (2004). It requires that the categories middle level readers (high school) must acquire 1500-3000 family words. Even though for the 3000 vocabulary level, they have not reached the threshold yet. While for the Social Science students, they reach half of the 1000 vocabulary level. While most of them got scores in 12 or 1200 vocabulary words and 9 or 900 vocabulary in the 2000 and 3000 vocabulary level. Based on this study, the students should be focused to learn high frequency vocabulary. As Webb (2017) stated that the high frequency vocabulary will give a bigger impact for the students. Since the high frequency vocabulary accounts for a large percentage of English, it provides a foundation for further lexical and language development for the students.Key Words: Vocabulary, Vocabulary Level Test, Natural science students and Social Sciencestudents.